Lessons Learned in Clinical Trial Communication During an Ebola Outbreak: The Implementation of STRIVE. (18th May 2018) - Callis, Amy; Carter, Victoria M; Ramakrishnan, Aparna; Albert, Alison P; Conteh, Lansana; Barrie, Alhaji Amadu; Fahnbulleh, Lucian; Koroma, Mark M; Saidu, Samuel; Williams, Otis; Samai, Mohamed
Abstract: Communication contributed to 4 important aspects of the Sierra Leone Trial to Introduce a Vaccine Against Ebola (STRIVE): recruiting participants, supporting Human Subjects Protection, building trust in the community to support the trial, and mitigating the impact of rumors and misinformation. Communication was particularly important because STRIVE was Sierra Leone's first vaccine clinical trial and was implemented during a public health emergency. Communication efforts began months prior to trial launch, building awareness and support through sensitization sessions with stakeholders and community leaders. Community engagement activities continued throughout the trial to maintain relationships with leaders and stakeholders and disseminate accurate information, fostering trust in the trial. The communication team led recruitment with hundreds of information sessions for potential participants, facilitating the informed consent process. Communication efforts continued post-enrollment, supporting ongoing voluntary participation in the trial. Informal formative activities during the trial yielded insights on participants' perceptions and information needs. While Centers for Disease Control and Prevention Institutional Review Board–approved activities and materials did not change, this flexible strategy allowed for responsive interactions with participants. The trial success and its community acceptance illustrated STRIVE's successful communications efforts, owing in large part to this flexibility and commitment to community engagement. Clinical Trials Registration: ClinicalTrials.gov [NCT02378753] and Pan African Clinical Trials Registry [PACTR201502001037220].